Peningkatan Program Literasi dan Numerasi di SMP Plus Baiturahman Dalam Rangka Implementasi Program Kampus Mengajar MBKM - Asri Widyasanti; Hafsah Hamidah; Cursor Fadila; Eka Desti Ramadhanita; Fina Aryadila (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
This research aims to implement various Kampus Mengajar programs Batch 5 in terms of improving literacy and numeracy skills at the elementary and secondary school levels. The school used as the object of placement in this study was SMP Plus Baiturrahman, located on Jalan Prof. KHM Sjadzli Hasan, Pasirwangi, Kec. Ujung Berung, Bandung City, West Java. The targets in this study were grade 8 students. The research was conducted for four months, from 20 February 2023 to 12 June 2023. The method used in this study was a descriptive method with a qualitative approach. The research was conducted through observation or direct observation and interviews with the school. This study's results were that various activities were carried out to improve students' literacy and numeracy skills during the assignment period for the Kampus Mengajar Program Batch 5 at Baiturrahman Plus Middle School. Some of these activities include AKM class tests, K-W-L Chart, Ular Tangga Games in learning, "Mading Berkreasi", “Be A Brilliant Writer” Activities, Siswa Berniaga, and Card Games in Statistics Learning. With these programs, it is hoped that it can improve the ability and quality of literacy and numeracy of students at SMP Plus Baiturrahman.